(untitled) (International journal of artificial intelligence, 2026)
Metabolic syndrome (MetS), a constellation of interconnected physiological, biochemical, clinical, and metabolic factors including central obesity, dyslipidemia, hypertension, and insulin resistance, significantly impacts the gastrointestinal system, particularly the gastric mucosa. This review synthesizes current evidence on the pathomorphological changes in the gastric mucosa driven by obesity-linked MetS, drawing from histopathological, microbiological, and molecular perspectives. Central to these alterations is the role of chronic low-grade inflammation induced by adipose tissue-derived cytokines, which disrupts mucosal homeostasis and promotes pathological remodeling. Studies indicate that obese individuals exhibit a higher prevalence of chronic gastritis (up to 80%), mucosal atrophy (around 30%), and intestinal metaplasia (15-20%), often compounded by Helicobacter pylori infection rates exceeding 50% in MetS cohorts. These changes are not isolated but part of a broader spectrum involving microbiome dysbiosis, where shifts in mucosa-associated bacteria—such as increased Proteobacteria and decreased Bacteroidetes—correlate with metabolic disturbances. Molecular analyses reveal upregulated inflammatory pathways like NF-κB and MAPK, alongside altered expression of adipokines such as leptin and adiponectin, which exacerbate epithelial damage and proliferative responses. Sex-specific differences emerge, with females showing potentially protective effects from estrogen on mucosal integrity, while males display more pronounced inflammatory infiltrates. Bariatric interventions, including sleeve gastrectomy, demonstrate reversal potential, with reduced macrophage infiltration and improved vascular density post-surgery. The global rise in obesity, affecting over one billion individuals, amplifies the urgency for understanding these mechanisms, as they predispose to severe outcomes like gastric adenocarcinoma. Advanced techniques, including proteomics and 16S rRNA sequencing, have illuminated these processes, highlighting therapeutic targets such as microbiome modulation and anti-inflammatory agents. This expanded analysis integrates epidemiological data, showing MetS prevalence in 25-30% of adults, and underscores the interplay between systemic metabolism and local gastric pathology. Longitudinal cohort studies further reveal that visceral adiposity metrics, like waist circumference, strongly predict mucosal alterations independent of BMI. The abstract emphasizes the multifactorial etiology, incorporating environmental factors like diet and genetics. Ultimately, early screening in at-risk populations could mitigate progression, fostering personalized medicine approaches in metabolic gastroenterology.